Enhancing Women's Entrepreneurial Competencies through Intensive English Training Integrated with the DreamBuilder LMS - Khartha, Aqzhariady; Alfian, Heri; Bohang, Muthmainnah Bahri A.; Suryadi, Ray; Pratiwi, Alifiah; Dakka, Litha Nesidekawati; Marhamah, Marhamah (Indonesian Journal of Community Services, 2025)
Program ini memperkenalkan pelatihan Bahasa Inggris intensif yang diintegrasikan dengan DreamBuilder Learning Management System (LMS) untuk meningkatkan keterampilan komunikasi bisnis dan kompetensi kewirausahaan bagi pengusaha perempuan. Pelatihan ini menggabungkan pembelajaran bahasa yang terarah dengan konten kewirausahaan melalui workshop interaktif, latihan peran, dan pembelajaran mandiri. Hasil evaluasi melalui pre-test, post-test, dan survei peserta menunjukkan peningkatan rata-rata sebesar 35,4% dalam kemahiran berbahasa Inggris, khususnya pada kosa kata bisnis, komunikasi tertulis, dan presentasi lisan. Peserta juga melaporkan peningkatan kepercayaan diri dalam memahami materi DreamBuilder serta dalam menggunakan Bahasa Inggris pada interaksi bisnis. Program ini menegaskan pentingnya integrasi antara pendidikan bahasa dan platform pembelajaran digital untuk mengatasi hambatan bahasa serta memberdayakan perempuan agar mampu bersaing secara efektif dalam lingkungan bisnis global.This program introduced an intensive English training initiative integrated with the DreamBuilder Learning Management System (LMS) to enhance the business communication skills and entrepreneurial competencies of women entrepreneurs. The training combined targeted language instruction with entrepreneurship-focused content through interactive workshops, role-playing, and self-directed learning. Evaluation through pre- and post-tests and participant surveys showed an average improvement of 35.4% in English proficiency, particularly in business vocabulary, written communication, and oral presentation. Participants also reported increased confidence in understanding DreamBuilder materials and using English in business interactions. The program underscores the importance of integrating language education with digital learning platforms to overcome language barriers and empower women to compete effectively in the global business environment.